Forest Fire Hotspots, Distribution and Management in Lowland of Tarai, Nepal - Karki, Gyanendra; Kunwar, Ripu; Khadka, Sushil; Adhikari, Shalu (Himalayan Biodiversity, 2025)
Spatial mapping, impact assessment and sustainable management of forest-fire in Nepal through participatory processes are urged in national policies; however, such attributes including identifying forest-fire hotspots and the management practices are handful in Nepal. This study aimed to provide the field-level information of forest-fire of Rautahat and Bara districts of Central lowland Tarai region that is helpful in mapping fire-hazardous areas and the related challenges, and developing management measures applying both GIS and participatory approaches. We used literature review, expert consultation, surveys with key informants and local communities, and integration with geocoordinate vector layers of seven variables (land use land cover, forest/vegetation type, aspect, slope, fire occurrence, proximity to settlement, and proximity to road) for GIS mapping and modeling of forest-fires. Results showed that forest-fire incidences are varied at spatio-temporal scales where annual forest-fires are increasing and influenced by human interferences. Forest-fire hotspots found in this study are closer to the built-up areas and villages, and prevalent in the northern part of villages, close to the Churia-Siwalik range and east-west highway. The northern parts are also associated with frequent open spaces abraded by invasive species, big shrubby patches, and dry, disturbed hardwood and mixed Sal forests that are annually burned by villagers for sprouts. Provided the warm and humid weather together with heavy pressure on forests for timber and non-timber forest products collection, the Sal forests of the villages and northern parts are under high risk of forest-fire. Engaging local communities in sustainable forest management measures and emphasizing and incentivizing forest-fire management interventions are some of the plausible ways forward.